THE ANALYSIS OF ENGLISH DEPARTMENT STUDENTS’ ABILITY IN MASTERING READING TEXT OF MUHAMMADIYAH ACEH UNIVERSITY - Siti Safura; Cut Mawar Helmanda (English Education Department, 2020)
The aim of this study is at examining how well the students’ ability in mastering the text and the main idea, and how they could improve their ability in understanding the text especially to find out the main idea from the text. The object of this study was 10 students from semester I in Intensive Reading Comprehension class. The data was obtained from the result of students’ worksheets and questionnaires distribution. In finding out the result, The data was analyzed by using descriptive qualitative. The result shows that the students’ ability in mastering reading text was categorized in poor level of understanding main idea. Besides, the result of questionnaire indicated that the main problem in reading lesson is that the methods used and the class situation. Therefore, the students do self motivation to enrich and memorize new vocabularies as an effort in improving their reading understanding. The implication of this study is to give the input to the lecturer of Reading subject to apply the appropriate method and technique, and create a nice class environtment.